Left Supraclavicular Lymph Node Recurrence after the Left Radical Nephrectomy: A Rare Presentation with Review of Literature (Indian Journal of Case Reports, 2019)
Renal cell carcinoma (RCC) presenting as left supraclavicular lymph node recurrence is rare, even though it can spread to any site in the body. There are very few cases of RCC with metastasis to the head and neck areas reported in the literature. Here, we report a case of clear cell carcinoma of RCC in a 16-year-old female who presented with the left supraclavicular recurrence after 5 months of radical nephrectomy. There were no metastasis foci identified elsewhere in the body. The patient was treated with sorafenib. After treatment, the lymph node regressed in size with no significant side effects. Clinicians and pathologists both should be aware of this unusual site of presentation during the evaluation of single-site metastasis in RCC.